1970
DOI: 10.1111/j.1432-1033.1970.tb01185.x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Function of a High‐Km Hexokinase in Immature Red Blood Cells

Abstract: The formation of 14C0, from [ l-14C]glucose and [6-14C]glucose by reticulocytes of rabbit and rat is dependent on the concentration of glucose over a wide range, indicating reactions preceding the formation of glucose-6-phosphate to be dependent on glucose concentration.I n haemolysates of rabbit reticulocytes a high-Km hexokinase was demonstrated by its kinetic properties. It corresponds to the glucokinase of liver. This enzyme does not occur in mature red blood cells of man and rabbit, nor in reticulocytes o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

1971
1971
2006
2006

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…The Km values found for glucose are the same in the hemolyzed cells and in the AS 45 fraction; the AS 75 fraction on the contrary showed a much higher Km value for glucose, similar to that of hepatic glucokinase (see below) and to that found by Gerber et al (8) for reticulocyte enzyme in hemolyzed rabbit red cells which are rich in reticulocytes.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…The Km values found for glucose are the same in the hemolyzed cells and in the AS 45 fraction; the AS 75 fraction on the contrary showed a much higher Km value for glucose, similar to that of hepatic glucokinase (see below) and to that found by Gerber et al (8) for reticulocyte enzyme in hemolyzed rabbit red cells which are rich in reticulocytes.…”
Section: Resultssupporting
confidence: 56%
“…Later, glucokinase was also found in other tissues (1,10,12,13,15,16,18,19,24). Its presence in mature circulating erythrocytes has been ex cluded, but it was found to be present in rabbit reticulocytes (8). We have carried out studies on the characteristics of erythrocyte enzymes and in particular on hexokinase which, due to its low turnover, deeply affects the entire eryth-1…”
mentioning
confidence: 99%
“…The details of the procedures were given in previous papers [25,60] hypoxic persons with an increased glucose 6-phosphate concentration [58]. I n that case the hexokinase activity was increased more than that of the phosphofructokinase.…”
mentioning
confidence: 99%
“…The possible significance of isoenzyme alterations during the development of cells is indicated in an article where the authors studied the isoenzymes of hexokinase as a function of the development of red blood cells (Gerber, Schultze & Rapoport, 1970). These workers found that the immature cells had a high-i^n, enzyme that was more suitable for the environment of the immature cells than the low-iCn, enzyme by which it was replaced in the adult cells.…”
Section: Isoenzymesmentioning
confidence: 99%